A state of the "heart": application of bioengineered materials for cardiac surgery - A. A. Sokol; D. A. Grekov; G. I. Yemets; A. Y. Galkin; N. V. Shchotkina; A. A. Dovghaliuk; N. M. Rudenko; O. V. Telehuzova; I. M. Yemets (Kazimierz Wielki University, 2020)
Introduction. Cardiovascular diseases have become the leading mortality cause, requiring a novel technologies and techniques for the treatment. Cardiovascular biomaterials play a vital role as the potentially eligible alternative modality for an operation, covering the gap between facilities and patients in need of medical devices and procedures. Purpose. The aim of this essay is to explore and analyze the currently used biomaterials for cardiac surgery as tools to repair or replace the damaged tissues. This study seeks to obtain data which will help to address research gaps and to stimuli the manufacturing process. Description of the state of knowledge. We conduct the systematic literature review, based on the information found in PubMed, Research Gate and Google Scholar databases using the eligible parameters. Obtained data in form of descriptive information were analyzed. Summary. This study has identified a wide area of cardiovascular biomaterials use in the modern clinical and scientific practice. The most obvious finding to emerge from this study is that decellularization of xenogenous heart valves is a crucial feature to obtain the optimal matrix for a tissue-engineered valve substitute. This information can be used to develop targetted interventions aimed at cardiac surgery.